Innovative Assessment Frameworks for Measuring Higher-Order Thinking Skills in Science Education - Ahmad Sofyan (Asian Journal of Applied Education (AJAE), 2026)
Science education requires assessment systems that go beyond measuring conceptual mastery to effectively evaluate students’ Higher-Order Thinking Skills (HOTS). However, school assessments remain dominated by low-level cognitive instruments, limiting HOTS development. This study aims to develop and test the effectiveness of an innovative assessment framework for measuring HOTS in science learning. Using a research and development approach, the study involved needs analysis, design, development, expert validation, and effectiveness testing through a quasi-experimental design. The participants were 60 eighth-grade students from a state junior high school in DKI Jakarta during the 2025/2026 academic year, divided into experimental and control groups. Data were collected using HOTS tests, student response questionnaires, and expert validation sheets, and analyzed using descriptive and inferential statistics. The results indicate that the developed assessment framework is highly valid and practical and significantly improves students’ HOTS compared to conventional assessments. This study contributes theoretically to the advancement of science education evaluation models and practically offers an effective assessment alternative to support HOTS-oriented learning at the junior high school level.